2020
DOI: 10.3390/ijms21144911
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Associated with Rheumatoid Arthritis Development and Antirheumatic Therapy Response

Abstract: Rheumatoid arthritis (RA) is the most common inflammatory arthropathy worldwide. Possible manifestations of RA can be represented by a wide variability of symptoms, clinical forms, and course options. This multifactorial disease is triggered by a genetic predisposition and environmental factors. Both clinical and genealogical studies have demonstrated disease case accumulation in families. Revealing the impact of candidate gene missense variants on the disease course elucidates understanding of RA molecular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 95 publications
0
39
1
3
Order By: Relevance
“…More than a hundred loci are associated with RA risk, most of which involve immune mechanisms [ 70 ]. The human leukocyte antigen (HLA) system, specifically HLA-DRB1 seems to be the most dominant, and it is related to peptide (and self-peptide) binding in pathogenesis [ 71 ].…”
Section: Zinc and Cadmium In The Aetiology And As Risk Factors Of mentioning
confidence: 99%
“…More than a hundred loci are associated with RA risk, most of which involve immune mechanisms [ 70 ]. The human leukocyte antigen (HLA) system, specifically HLA-DRB1 seems to be the most dominant, and it is related to peptide (and self-peptide) binding in pathogenesis [ 71 ].…”
Section: Zinc and Cadmium In The Aetiology And As Risk Factors Of mentioning
confidence: 99%
“…Its clinical manifestation is multiple arthritis of the small joints of the hands and feet, which can lead to joint pain, injury and even loss of function, and seriously affects the quality of life of patients [39]. At present, the pathogenesis of rheumatoid arthritis is not very clear, but most studies believe that T lymphocytes and macrophages release a large number of in ammatory cytokines to cause bone and joint damage in rheumatoid arthritis [40].…”
Section: Discussionmentioning
confidence: 99%
“…A complex interaction between genotype and exposure to environmental factors (cigarette smoking, air pollutants, and occupational dust) is likely to determine the onset and development of RA [ 5 ]. Genetic studies have found an association of more than 100 polymorphisms with RA, mainly in the major histocompatibility complex (MHC) locus, but also in genes encoding for cytokines/chemokines and their receptors, components of intracellular signaling pathways, and costimulatory factors [ 6 ]. The implication of genetic factors in the RA pathogenesis is demonstrated by a positive family history, which increases the risk of RA by about three to five times [ 4 , 7 ].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%